Comparison of UN and THE USA activities in the process of developing the countries: Kosovo and Iraq case - Marinko Jurilj; Domagoj Galić (Hum, 2012)
New security threat appeared after the Cold War: expanding of instability became a real danger because of ruined countries which cannot control their own territory. Developing a country is a more demanding work than developing public institutions; that requires creating political, economic and military conditions for keeping permanent peace. Political analysts cannot agree on the issue related to internationally sponsored developing of countries; some call it neocolonialism, while the others say that process of developing the country is necessary not only because of security but also because of humanitarian reasons. Two typical examples of developing the country are Kosovo and Iraq – both went through the war and destroying authorities. UN took over the main role in Kosovo, while the USA took over the process of developing the country in Iraq. In this paper analysis of developing the country in Iraq and Kosovo served for showing differences in UN approach from one side and the USA approach from the other side.